2019
DOI: 10.1155/2019/8568920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spices on the Formation of VOCs in Roasted Mutton Based on GC-MS and Principal Component Analysis

Abstract: Peppertree prickly ash, Amomum tsao-ko, cumin, and ginger have long been used in Asian countries to modify the flavor and to partially neutralize any unpleasant odors present in roast lamb. The purpose of this study was to evaluate the change in the amount of volatile components present in roast lamb compared to meat added with peppertree prickly ash, Amomum tsao-ko, cumin, and ginger. Principal component analysis was carried out on the 27 initially selected from 88 volatile substances, and 15 substances with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…The formation of soup aroma may include oxidation and thermal degradation of lipids, rib nucleotides, and thiamine, the interaction between sugars and TA B L E 4 (Continued) amino acids (or peptides), as well as the pyrolysis of amino acids and peptides. In addition, the secondary reactions may occur between the products of these primary reactions and made further efforts to contribute to the development of mutton flavor (Xi et al, 2019).…”
Section: Analysis Of Volatilesmentioning
confidence: 99%
“…The formation of soup aroma may include oxidation and thermal degradation of lipids, rib nucleotides, and thiamine, the interaction between sugars and TA B L E 4 (Continued) amino acids (or peptides), as well as the pyrolysis of amino acids and peptides. In addition, the secondary reactions may occur between the products of these primary reactions and made further efforts to contribute to the development of mutton flavor (Xi et al, 2019).…”
Section: Analysis Of Volatilesmentioning
confidence: 99%
“…Moreover, prickly ash ( Zanthoxylum bungeanum Maxim) is popular and widely used in the meat processing. Xi et al found that the addition of spices can modify flavor and partially neutralize unpleasant odors present in roast sheep meat, and prickly ash improved the content of terpenes greatest [ 19 ]. The prickly ash is rich in flavonoids and amides, which has been reported with bitter taste [ 20 ] and pungent sensation [ 21 ], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Headspace solid phase microextraction (HS-SPME) integrates sampling, extraction, concentration and sample injection, which greatly improves the efficiency of detection and analysis of volatile compounds [ 9 ]. Many researchers have used HS-SPME combined with GC-MS to comprehensively evaluate the flavor compounds of roasted lamb [ 2 , 7 , 10 ], stir-fried pork slices [ 11 ], roasted beef [ 12 ] and smoked chicken [ 13 ]. Free amino acid and 5′-nucleotides are typical nonvolatile compounds in meat products.…”
Section: Introductionmentioning
confidence: 99%